ANALISIS PERBANDINGAN METODOLOGI SIYASAH SYAR’IYYAH DENGAN USUL AL-FIQH - Abdul Rahman, Mohamad Zaidi (Jurnal Syariah, 2019)
Studies in the field of siyasah shar’iyyah can’t be separated from using the same sources of hukm as implemented in the field of UUl al-fiqh. This is due to the fact that, hukm is one of the vital elements employed in analyzing siyasah shar’iyyah condition. However, question arises whether the exercise of those sources on UUl al-fiqh can be treated similarly on siyasah shar’iyyah. Thus, the aim of this article is to examine whether there is a relationship between siyasah shar’iyyah and UUl al-fiqh. On the other hand, the study is trying to explore the dissimilarity of the types of methodology used in both of them.